Beyond America: Cross-national Context and the Impact of Religious Versus Secular Organizational Membership on Self-rated Health. (August 2018) - Upenieks, Laura; Foy, Steven L.; Miles, Andrew
Studies using data from the United States suggest religious organizational involvement is more beneficial for health than secular organizational involvement. Extending beyond the United States, we assess the relative impacts of religious and secular organizational involvement on self-rated health cross-nationally, accounting for national-level religious context. Analyses of data from 33 predominantly Christian countries from the 2005–2008 World Values Survey reveal that active membership in religious organizations is positively associated with self-rated health. This association's magnitude is higher than the magnitude of associations between many memberships in secular organizations and health. The positive association between involvement in religious organization and self-rated health is moderated by national levels of religious pluralism such that positive associations are primarily found in nations high in religious diversity. These results replicated in a sample of 21 majority-Christian nations from the 2010–2014 World Values Survey.